SRG/eROSITA-triggered XMM-Newton observations of three Be/X-ray binaries in the LMC: Discovery of X-ray pulsations - Haberl, F.; Maitra, C.; Kaltenbrunner, D.; Buckley, D. A. H.; Monageng, I. M.; Udalski, A.; Doroshenko, V.; Ducci, L.; Kreykenbohm, I.; Maggi, P.; Rau, A.; Vasilopoulos, G.; et al. (2023)
Context. Using data from eROSITA, the soft X-ray instrument aboard Spectrum-Roentgen-Gamma (SRG), we report the discovery of two new hard transients, eRASSU J050810.4-660653 and eRASSt J044811.1-691318, in the Large Magellanic Cloud. We also report the detection of the Be/X-ray binary RX J0501.6-7034 in a bright state. Aims: We initiated follow-up observations to investigate the nature of the new transients and to search for X-ray pulsations coming from RX J0501.6-7034. Methods: We analysed the X-ray spectra and light curves from our XMM-Newton observations, obtained optical spectra using the South African Large Telescope to look for Balmer emission lines and utilised the archival data from the Optical Gravitational Lensing Experiment (OGLE) for the long-term monitoring of the optical counterparts. Results: We find X-ray pulsations for eRASSU J050810.4-660653, RX J0501.6-7034, and eRASSt J044811.1-691318 of 40.6 s, 17.3 s, and 784 s, respectively. The Hα emission lines with equivalent widths of −10.4 Å (eRASSU J050810.4-660653) and −43.9 Å (eRASSt J044811.1-691318) were measured, characteristic for a circumstellar disc around Be stars. The OGLE I- and V-band light curves of all three systems exhibit strong variability. A regular pattern of deep dips in the light curves of RX J0501.6-7034 suggests an orbital period of ∼451 days. Conclusions: We identify the two new hard eROSITA transients eRASSU J050810.4-660653 and eRASSt J044811.1-691318 and the known Be/X-ray binary RX J0501.6-7034 as Be/X-ray binary pulsars.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics; Be; galaxies: individual: LMC; stars: emission-line; stars: neutron; X-rays: binaries